Dual modes of DNA N 6 -methyladenine maintenance by distinct methyltransferase complexes - Yuanyuan Wang; Bei Nan; Fei Ye; Zhe Zhang; Wentao Yang; Bo Pan; Fan Wei; Lili Duan; Haicheng Li; Junhua Niu; Aili Ju; Yongqiang Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Stable inheritance of DNA N 6 -methyladenine (6mA) is crucial for its biological functions in eukaryotes. Here, we identify two distinct methyltransferase (MTase) complexes, both sharing the catalytic subunit AMT1, but featuring AMT6 and AMT7 as their unique components, respectively. While the two complexes are jointly responsible for 6mA maintenance methylation, they exhibit distinct enzymology, DNA/chromatin affinity, genomic distribution, and knockout phenotypes. AMT7 complex, featuring high MTase activity and processivity, is connected to transcription-associated epigenetic marks, including H2A.Z and H3K4me3, and is required for the bulk of maintenance methylation. In contrast, AMT6 complex, with reduced activity and processivity, is recruited by PCNA to initiate maintenance methylation immediately after DNA replication. These two complexes coordinate in maintenance methylation. By integrating signals from both replication and transcription, this mechanism ensures the faithful and efficient transmission of 6mA as an epigenetic mark in eukaryotes.